Analysis of pedestrians' perception of accessibility and urban mobility conditions of sidewalks and sidewalks in the municipality of Abaetetuba, Pará, Brazil (Research, Society and Development, 2022)
Sidewalks and sidewalks must guarantee the movement of people with autonomy, regardless of their limitations, being necessary to present conditions of fluidity, comfort and safety. Physical barriers tend to reduce accessibility conditions on sidewalks and sidewalks, making it difficult to move, especially for people with reduced mobility. In the municipality of Abaetetuba, Pará, the problem of urban mobility related to public places is common. This study sought to gather information about the perception of users of public walkways and sidewalks in the urban center of the city. Through a semi-structured questionnaire, 95 people were interviewed, with ages ranging from 30 to 89 years. It was observed a large number of people with more advanced age, and who need to move through these public spaces in a safe way. In addition, 31.5% of respondents reported suffering from some physical limitation and 56% reported having already suffered an accident due to the poor condition of sidewalks and public walkways. The main problem reported by respondents was the occurrence of uneven sidewalks and/or with holes, cited by 81% of respondents. The study enabled a greater understanding of the perception of pedestrians regarding the public spaces used, as well as indications that can guide public decisions in decision-making at the time of conceptions and reforms of public works, in addition to stimulating the guidance and inspection of private works.